HOUSEHOLD ACCOUNTING: BENARKAH MENCEGAH FAMILY DISHARMONY? - Mulyani, Mulyani; Yunita, Khristina; Ginting, Rafles (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2024)
The phenomenon that occurs nowadays is that many wives work, so it is necessary to manage household finances so that income can be managed well and avoid unwise behavior in using money. This research aims to reveal the responses of working wives and non-working wives in responding to household financial transparency and the implementation of household accounting in the family in order to create financial transparency. Qualitative data collection methods used in this research include interviews, observation and documentation studies. The results of this research show that accounting in the household has an important role in household life, namely being able to determine the distribution of income and expenditure in the household. Mental accounting is a person's behavior in dealing with their finances by arranging, dividing and allocating the money they have into accounts or categories according to their needs so that the money they have can be used effectively and efficiently. By carrying out household financial transparency, you can increase trust in your husband because the wife is open and honest about the household's financial condition, which can increase feelings of love, thereby increasing household harmony.